Determinants of the development of corporate bond markets in Argentina: One size does not fit all - Roque B. Fernández; Sergio Pernice; Jorge M. Streb (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2007)
Conventional theory leads to expect bonds to be a financing vehicle for large firms because of economies of scale and contracting costs. We find both in our econometric evidence for firms quoted on Latin American stock exchanges, and in our survey results for Argentina, that size of assets is a robust determinant of the use of bond finance. This result, together with the fact that there are few firms that are large in terms of market value, can help understand why Argentina, as well as Latin America, has small bond markets in terms of the ratio of the stock of bonds to GDP. Since firm value represents the present value of the cash flows against which the firm borrows, the outstanding stock of corporate bonds is as small as the size of Argentine firms.
Keywords: G3; E6; 330; debt structure; leverage; short term debt; corporate bonds; firm size; firm value; Unternehmensanleihe; Argentinien